Asuhan Kebidanan Pada Bayi Baru Lahir Di PMB Nurwati Di Wilayah Kerja Puskesmas Air Tiris Tahun 2022 - Nababan, Fitriani; Mayasari, Endang (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
Newborns are babies born from 37 – 42 weeks of gestation with a birth weight of 2500 – 4000 grams. During this period, there was a very big change from life which was originally in the womb, completely dependent on the mother, to outside the womb, which had to live independently. Providing Midwifery Care using a midwifery management approach to Newborns at PMB Nurwati in the Air Tiris Health Center Working Area in 2022. This study used a descriptive observational method with a case study approach that aims to determine midwifery care. This study conducted an assessment and collection of basic data is the initial stage of midwifery management using SOAP with a Varney mindset, namely subjective data assessment, objective data assessment, assessment and the appropriate management according to the problems complained of by Baby Ny. I is Normal Newborn Baby. Data collected by researchers through direct examination of newborns with their parents and their closest family. Based on the care given to the baby, Mrs. I have been given care for 8 days. The midwifery care carried out was preventing heat loss, cleaning the airway, cutting and caring for the umbilical cord, giving an IMD, performing a physical examination, administering vitamin K injection, giving eye ointment, hospitalization, bathing the baby, swaddling the baby, and giving HB0 immunization. About the danger signs, keeping the baby warm, teaching how to breastfeed properly and properly